Enhancement Of Cellulase-Poor Xylanase Production By Native Fungi Via Solid State Fermentation Process - Tai, Wan Yi (2016)
High cost of cellulases remains the most significant barrier to the economical production of bio-ethanol from lignocellulosic biomass (LB). The present study aims at developing a local cellulolytic fungal strain with enhanced cellulolytic ability through random mutagenesis coupled with the feasibility of solid-state fermentation (SSF) by utilizing oil palm frond (OPF) as the substrate. Out of 95 wild isolates isolated from agricultural sites and tested both qualitatively and quantitatively, a native filamentous fungal strain designated DWA8 was found to be the top enzymatic secretor. During qualitative screening, 38 isolates were found to produce distinctive halo but only 23 were chosen to proceed with quantitative screening. For quantitative enzyme analysis, enzyme supernatant was extracted from the SSF process which was conducted using IxlO6 spore/mL inoculated onto 5 g of ground OPF, incubated at room temperature for 7 days. DWA8 was found to be the best candidate for further studies, as it produced the highest amount of fpase and xylanase with a considerably high amount of cmcase, which Aspergillus niger (Genebank accession no. KP299287) based on colony morphology and the best cultivation period where the cmcase, fpase and xylanase activities of A. niger DWA8 were 1.13 U/g, 2.55 U/g and 2.38 U/g respectively.